2022
DOI: 10.1097/inf.0000000000003792
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Postacute Clinical Characteristics of Coronavirus Disease 2019 in Children in Japan

Abstract: Background: The clinical features of coronavirus disease 2019 (COVID-19) in children have been changing because of the emergence and rapid spread of variants of concern (VOC). The increase in cases infected with VOC has brought concern with persistent symptoms after COVID-19 in children. This survey aimed to analyze the clinical manifestations and persistent symptoms of pediatric COVID-19 cases in Japan. Methods: We analyzed the clinical manifestations of pediatric COVID-19 cases reported between February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…9 In our cohort, fever was significantly more frequent during LO period (87% compared to 79% during EO), but the prevalence of febrile seizures was low and did not differ according to the analyzed periods (1.5% during LO, and 0.87% during EO). Fever was found by other authors to occur more frequent during the Omicron wave compared to previous variants, 8,9,11 which may lead to an increase in the incidence of febrile seizures. In addition, most studies reported that children suffering from COVID-19 during the Omicron wave were significantly younger than in previous periods, [10][11][12] which may contribute to a more frequent occurrence of febrile seizures or croup, which are typically seen more often in younger children.…”
Section: Discussionmentioning
confidence: 69%
“…9 In our cohort, fever was significantly more frequent during LO period (87% compared to 79% during EO), but the prevalence of febrile seizures was low and did not differ according to the analyzed periods (1.5% during LO, and 0.87% during EO). Fever was found by other authors to occur more frequent during the Omicron wave compared to previous variants, 8,9,11 which may lead to an increase in the incidence of febrile seizures. In addition, most studies reported that children suffering from COVID-19 during the Omicron wave were significantly younger than in previous periods, [10][11][12] which may contribute to a more frequent occurrence of febrile seizures or croup, which are typically seen more often in younger children.…”
Section: Discussionmentioning
confidence: 69%
“…22,23 Thirdly, the increase in febrile seizure and gastrointestinal symptoms among children with COVID-19 during Wave VI and VII contributed to the elevated use of ambulances, antiepileptics and antiemetics, as well as higher levels of creatinine phosphokinase and aspartate aminotransferase in our findings. 5–7…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Thirdly, the increase in febrile seizure and gastrointestinal symptoms among children with COVID-19 during Wave VI and VII contributed to the elevated use of ambulances, antiepileptics and antiemetics, as well as higher levels of creatinine phosphokinase and aspartate aminotransferase in our findings. [5][6][7] The decreasing trends in total healthcare costs and length of hospital stay reflected the changes in the discharge criteria defined by the Ministry of Health, Welfare and Labor and local governments in Japan. During the earlier waves, the discharge criteria were strict, which included 2 consecutive negative results of a nucleic acid amplification test or antigen test following symptom improvement for inpatients with nonsevere COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of seizures in children aged 1-4 years, which was 1.3% before the Delta variant outbreak, increased to 13.4% during the Omicron variant period. 33 Infants and preschool-aged children accounted for 65.1% of severe and moderate pediatric cases during the Omicron variant period. Between January and September 2022, a total of 62 deaths due to COVID-19 were confirmed in individuals under the age of 20, with children under 5 years old representing approximately half of these cases.…”
Section: Respondents No (%)mentioning
confidence: 99%